Notion of Personal Statute of Legal Person (lex societatis) and Criterions of its Determination - M. A. Manukyan (Московский журнал международного права, 2009)
In the literature on private international law, there are certain terms, which characterize the legal connection between legal persons and a state. On the base of interdisciplinary method, the article firstly analyzes the notions lex societatis, personal law, personal (corporate) statute, state belonging, nationality, domicile and residence of the company and reveals their legal nature and application in various jurisdictions. It is noted that in the contemporary times of legal developments in private international law, the notion “nationality” in relation to companies loses its practical value and becomes obsolete. It is mentioned about the belief of the author regarding inexpediency of application of the notion “nationality” in private international law. The article, secondly, explores the main approaches of determination of personal law of the company: incorporation, real seat and main place of business. The advantages and disadvantages of incorporation and real seat theories were illustrated in light with the law and practice of various states. Furthermore, the theory of control is explored in light with the French, American and British case law and practice of International Court of Justice. The article gives an idea of recent cases of European Court of Justice and specifies that the real seat theory has been put aside in the EC after Centros, Überseering and Inspire Art.